Effects of Curing Modes of Light Emitting Diode on Shear Bond Strength of Resin Composite - Kasim A Mohammad; Mohammad Gh Hamdoon; ALi M Rasheed (University of Mosul, College of Dentistry, 2008)
Aim: To evaluated the SBS of three resin composites (Tetric Flow, Tetric and Heliomolar) bonded to dentin and cured by different curing modes utilizing light emitting diode (LED) light curing unit. Materials and Method: Buccal dentin of 90 upper premolars was expose and Clearfil SE Bond applied and cured prior to restorative procedure. Samples divided into 9 groups (3 groups for each composite type), photoactivation of groups of each composite was carried out using three modes: Continuous (CO: 600 mW/cm2 for 40 s), Soft-Start (SS: 100 mW/cm2 for 10 s + 600 mW/cm2 for 30 s) and Pulse-Delay (PD:100 mW/cm2 for 3 s + 3 min wait + 600 mW/cm2 for 37 s). Samples thermocycled and loaded at toothcomposite interface at 1 mm/min cross head speed until failure. Results: Two-way ANOVA (p < 0.05) followed by Duncan multiple range test revealed that SBS of SS mode (21.5 Kg) is significantly higher than SBS of both CO (18.1 Kg) and PD (18.7 Kg) and its also revealed that although SBS of Tetric Flow (21.2 Kg) is higher than that of Tetric (20.1 Kg) and both are significantly higher than that of Heliomolar (16.9 Kg).Conclusions: Less material's rigidity along with slower polymerization reaction by SS mode result in higher SBS due to lesser contraction stress at the adhesive interface